2007
DOI: 10.2220/biomedres.28.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laughter on salivary endocrinological stress marker chromogranin A

Abstract: We investigated the effect of laughter on salivary endocrinological stress marker chromogranin A (CgA). In saliva samples collected from 11 healthy males before and after watching a comic film or a non-humorous control film, salivary CgA levels were determined by enzyme-linked immunosorbent assay (ELISA). Samples taken after watching the comic film showed increased levels of CgA. This tendency was more pronounced in individuals with lower initial levels of stress. The control samples showed no significant chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 14 publications
2
18
0
1
Order By: Relevance
“…In particular, chromogranin A (CgA), an acidic peptide stored by the adrenal medulla and coreleased with catechlamines, has become more accepted in studies of the endocrine acute stress response. Salivary CgA was found to increase rapidly during prolonged noise (45 ) and to decrease significantly in individuals being tested in a setting with humorous content (46 ). Accordingly, CgA in saliva could be a valuable parameter for measuring acute stress response under controlled study conditions.…”
Section: Researchmentioning
confidence: 97%
“…In particular, chromogranin A (CgA), an acidic peptide stored by the adrenal medulla and coreleased with catechlamines, has become more accepted in studies of the endocrine acute stress response. Salivary CgA was found to increase rapidly during prolonged noise (45 ) and to decrease significantly in individuals being tested in a setting with humorous content (46 ). Accordingly, CgA in saliva could be a valuable parameter for measuring acute stress response under controlled study conditions.…”
Section: Researchmentioning
confidence: 97%
“…The CgA levels of the saliva samples collected before and after the stress task were analyzed. In addition, stress was measured subjectively before and immediately after the stress task using a ten-division visual analog scale (VAS) (27).…”
mentioning
confidence: 99%
“…Its level has been reported to transiently increase in response to short-term stressors such as a calculation test [4], white noise [19], and a cognitive test [20]. However, a recent study showed a transient increase in the CgA level after watching a comic video [21]. This study also indicated that the elevation in CgA levels was remarkable in the subjects who experienced lower daily stress.…”
Section: Cgamentioning
confidence: 66%